2004
DOI: 10.1080/09687630410001668960
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent psychological health problems and delinquency among volatile substance users in a school sample in South London

Abstract: The study assessed prevalence of volatile substance abuse (VSA), and its link to other forms of psychoactive substance use and to other problem behaviours among 14-15 year olds recruited from sixteen secondary schools in south-west London. Lifetime use of volatile substances was reported by 126 young people (6% of the sample) whose mean age of first use was 12.6 years. Using logistic regression analysis, lifetime use of volatile substances was found to be associated with more frequent cigarette smoking and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Incarcerated adolescents overwhelmingly tend to have more severe psychopathology than their counterparts in the community (e.g., Teplin et al, 2002), so a study of exclusively incarcerated youth may exaggerate or otherwise distort the association between inhalants and suicidality. However, it is notable that studies using community or school-based samples of adolescents have consistently demonstrated a relationship between inhalant use and suicidal thoughts (Best et al, 2004) or suicide attempts (Garofalo et al, 1999;Wilcox and Anthony, 2004). Inhalant use and suicidality have remained associated in other specialized samples, including Inuit youth (Kirmayer et al, 1998), adolescents with a substance use disorder (Kelly et al, 2004) or behavioral problems (Sakai et al, 2004), students in an alternative high school (Fleschler et al, 2002), and youth on criminal probation (Howard and Jenson, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incarcerated adolescents overwhelmingly tend to have more severe psychopathology than their counterparts in the community (e.g., Teplin et al, 2002), so a study of exclusively incarcerated youth may exaggerate or otherwise distort the association between inhalants and suicidality. However, it is notable that studies using community or school-based samples of adolescents have consistently demonstrated a relationship between inhalant use and suicidal thoughts (Best et al, 2004) or suicide attempts (Garofalo et al, 1999;Wilcox and Anthony, 2004). Inhalant use and suicidality have remained associated in other specialized samples, including Inuit youth (Kirmayer et al, 1998), adolescents with a substance use disorder (Kelly et al, 2004) or behavioral problems (Sakai et al, 2004), students in an alternative high school (Fleschler et al, 2002), and youth on criminal probation (Howard and Jenson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 21.9% of inhalant users in a study of Massachusetts high school students reported a suicide attempt in the previous year, compared to 6.8% of non-users in that study (Garofalo et al, 1999). In general, studies indicate that youth with prior suicidality are more likely to report inhalant use (Fleschler et al, 2002;Howard and Jenson, 1999) than nonsuicidal youth and that inhalant use relates to increased reports of suicidal ideation (Best et al, 2004) and suicide attempts (Kelly et al, 2002;Kelly et al, 2004;Sakai et al, 2004). A rare prospective study of inhalant use and suicidality found that youth who used inhalants before age 16 were almost two times more likely, relative to non-users, to later attempt suicide, even when controlling for potential confounders (Wilcox and Anthony, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…While only 2.9% of nondrinkers and non-smokers had ever used an illicit drug, this was the case for 45.7% of those who had both drunk alcohol and smoked cigarettes in the previous month. In more recent work in the same areas of south London, using the same database as reported in this study, Best et al [20] found that lifetime use of solvents was associated with more frequent use of cannabis in the school sample assessed.…”
Section: Introductionmentioning
confidence: 61%
“…In 2004 9.6% of US 8th graders and 8% of English secondary students reported VSM during the previous year (Blenkinsop et al, 2004;Johnston, O'Malley, Bachman, & Schulenberg, 2005). Chronic or dependent use is unusual and often co-occurs with a range of other lifetime difficulties including poverty, mental health problems, other problematic drug use, abuse, family conflict and homelessness, poor schooling achievement and involvement with the justice and child welfare systems (see for example Best et al, 2004;Howard & Jenson, 1999;Kurtzman, Otsuka, & Wahl, 2001;Sakai, Hall, Mikulich-Gilberts, & Crowley, 2004;Worley, 2001). A study of adolescents in the UK found that only 0.4% of respondents met the DSM-IV criteria for inhalant abuse or dependence (Wu, Pilowsky, & Schlenger, 2004).…”
Section: Patterns Prevalence Problems and Preventionmentioning
confidence: 96%